Psychosocial and cognitive multimorbidity and health-related quality of life and symptom burden in older adults with atrial fibrillation: The systematic assessment of geriatric elements in atrial fibrillation (SAGE-AF) cohort study. (September 2020) - Bamgbade, Benita A.; Sanghai, Saket R.; McManus, David D.; Lessard, Darleen; Waring, Molly E.; Forrester, Sarah; Pierre-Louis, Isabelle; Saczynski, Jane S.
Highlights: Psychosocial (depression and anxiety) and cognitive impairment is common among older adults with atrial fibrillation. Psychosocial and cognitive multimorbidity is associated with higher odds of poor health-related quality of life and high symptom burden. Psychosocial and cognitive screening may identify a population at high-risk for poorer health outcomes. Abstract: Background: Depression, anxiety, and cognitive impairments occur in up to 40 % of adults with AF and are associated with poorer health-related quality of life (HRQoL) and higher symptom burden. However, it is unknown how often these impairments co-occur, or multimorbidity, and how multimorbidity effects HRQoL and symptom burden. Methods: Patients with AF age ≥65 years with a CHA2 DS2 VASC risk score ≥ 2 and eligible for oral anticoagulation therapy were recruited from five clinics in a prospective cohort study. Participants completed validated measures of depression (PHQ9) and anxiety (GAD7), cognitive impairment (MoCA), and HRQOL and AF symptom burden (AFEQT). Multinomial logistic regression was used. Results: Participants (N = 1244, 49 % female) were on average 76 ± 7 years; 86 % were non-Hispanic white. Approximately 35 % of participants had 1 impairment, 17 % had 2 impairments and 8% had 3 impairments; 39 % had none of the 3 impairments examined. Compared to participants with no impairments, patients with 1, 2 and 3 impairments had higher odds of poor HRQoL (adjusted OR [AOR] = 1.77, 95 % CI 1.21, 2.60; AOR = 6.64, 95 % CI 4.43, 9.96; and AOR = 7.50, 95 % CI 4.40, 12.77, respectively) and those with 2 and 3 impairments had higher odds of high symptom burden (AOR = 3.69 95 % CI 2.22, 6.13; and AOR = 5.41 95 % CI 2.85, 10.26). Conclusions: Psychosocial/cognitive multimorbidity is common among older adults with AF and is associated with poor HRQoL and high symptom burden. Clinicians might consider incorporating psychosocial and cognitive screens into routine care as this may identify a high-risk population.